Polarized Historical Preservation Trajectories: Comparative Studies of Tongli Town and Yaowan Town - Liu Yihan; Li Jianwei (Lodz University of Technology Press, 2023)
Due to the divergences of social-economic and cultural environments in the different regions, the existing conditions of historical towns in China emerge into two radical morphological forms, Static Town and Kinetic Town. In 2008, to avoid extreme dichotomic development situations and keep the authenticities of historical towns, the Chinese Historical Town Preservation Bureau formulated a standardized regulation, ‘Regulation on the Protection of Famous Historical and Cultural Cities, Towns and Villages’ (abbreviated 2008 Regulation – 历史文化名城名镇保护条例2008). However, this 2008 Regulation resulted in two trajectories of redeveloping historical towns: government-driven and market-driven preservation approaches, accelerating the disparity of these two morphological forms. This paper reveals the morphologies differentiations of these two outcomes through the lens of demographic migration, economic structure, natural resource and social-spatial structure by comparing two renowned historical town redevelopment projects: the role model, Tongli Historical Town, as a Static Form, located in the wealthy South of Jiangsu Province and the controversial case, Yaowan Historical Town, as a Kinetic Form, located in less developed Northern Jiangsu Province. Eventually, this article explores the reasons behind the inevitability of the polarized historical trajectories' emergence and provides a comprehensive reinterpretation of the extremes triggered by the 2008 Regulation.
Keywords: historical town conservation; urban morphology; social-spatial structure; natural resource; Tongli and Yaowan; ochrona miast historycznych; morfologia miast; struktura społeczno-przestrzenna; zasoby naturalne; Tongli i Yaowan